Molecular evaluation of E198A SNP in the iso-type 1 β – tubulin gene of Haemonchus contortus isolated from sheep in Al-Diwanyiah, Iraq - Akram M. Amana; Mansoor J. Alkhaled (Iraqi Journal of Veterinary Sciences, 2023)
This study investigated the benzimidazole resistance in Haemonchus contortus parasitic nematodes from sheep from October 2021 to December 2022 in Al-Diwanyiah city/Iraq, and samples were processed at the laboratory of Parasitology in Veterinary Medicine College of Al-Qadissyiah University through the detection of E198A mutation and SNP polymorphism of the β-tubulin gene at this codon position. Ninety adult H. contortus samples were collected from the abomasum of sheep (n = 400) and then tested by qPCR and tetra-primer ARMS-PCR. Of these, three different genotypes have been found for E198A SNP: heterozygous (RS), homozygous (SS), and homozygous resistant genotype (RR). The frequencies for these genotypes were 31.11% heterozygous, 57.77% homozygous, and 11.11% homozygous resistant. The current study indicated the spread of benzimidazole resistance for H. contortus of sheep in Iraq, Al-Diwnayiah by utilizing qPCR and tetra-primer ARMS-PCR for the first time. It is speculated that the BZ-resistance is due to excessive and irregular H. contortus drug abuse and inter-species transfer between ruminants at the commonly grazing pastures and from imported sheep.